Visitor perceptions and reliance on active and passive communication techniques in zoos - Foote, Dustin J.; Louder, Matthew I. M.; Balakrishnan, Christopher N. (PeerJ Preprints, 2017)
The goal of educating the public about environmental and conservation issues is found in the mission statements of almost every zoo in the world. In order to effectively teach their visitors, zoos must understand how they are communicating with their public. In this study, we attempt to quantify how Sylvan Heights Bird Park (SHBP) communicates with its visitors. SHBP is a small not-for-profit facility that specializes in birds, with a primary focus on waterfowl (Anseriformes). Located in an economically depressed eastern North Carolina county (Halifax), SHBP receives over 46,000 visitors a year. Using a survey, we collected information of visitor perceptions of the role of zoos, their reliance on different sources of information, and their retention of information provided via different modes of communication. SHBP visitors listed exhibit signage (passive communication) as the preferred method of gaining information. Interestingly, however, we found that reliance on signage varied with age and gender and we found no difference in information retention between visitors that experienced only passive communication (signage) versus those that experienced active communication. Just over half (51%) of visitors viewed the primary purpose of a zoo to be entertainment but this view changed with age and gender. Although almost all respondents identified the role of zoos in maintaining biodiversity, we found a disconnect between this view and an understanding of how zoos might contribute to species conservation.
Keywords: communication; survey; conservation; biodiversity; active learning; passive learning; public education; informal learning; education exhibit